MEMAHAMI REKSADANA SYARIAH: INSTRUMEN KEUANGAN BERBASIS SYARIAH - Sumar'in Sumar'in (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
In finance, investment is buying or creating an asset with the expectation of capital appreciation, dividends (profit), interest earnings, rents, or some combination of these returns. This may or may not be backed by research and analysis. Most or all forms of investment involve some form of risk, such as investment in equities, property, and even fixed interest securities which are subject, among other things, to inflation risk. A mutual fund is simply a financial intermediary that allows a group of investors to pool their money together with a predetermined investment objective. The mutual fund will have a fund manager who is responsible for investing the pooled money into specific securities (usually stocks or bonds). The ruling with regards to mutual funds from an Islamic perspective can be determined by understanding the Shar’i ruling on shares and bonds.